(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The investigation reported in this paper was carried out to study the feasibility of using steel scrap obtained from lathe machine in fibre reinforced concrete by checking the compressive strength and splitting tensile strength of M20 concrete and thus optimizing the fibre proportions.